THE CONSTITUTION OF A DEMOCRATIC STATE AS A REGULATION OF STATE INSTITUTIONS: A STATE SCIENCE PERSPECTIVE - Aznaya Kirana Maudiva; Chintia Sandi; Fawazi Rihadatulaisy Mulyadi (Catalist Indo Publisher, 2026)
This study aims to analyze the urgency of strengthening the principle of constitutionalism within Indonesia’s constitutional framework and to formulate recommendations for future improvements. The method employed is a normative juridical approach through an examination of legislation and evolving constitutional practices. The results indicate that the implementation of constitutionalism in Indonesia still faces several challenges, including a weak legal culture, overlapping authority among state institutions, and an underdeveloped system of checks and balances. Therefore, clearer institutional arrangements, the strengthening of public constitutional awareness through education, and regulatory reforms oriented toward legal certainty and justice are necessary. In conclusion, strengthening constitutionalism is a strategic step toward realizing a democratic, transparent, and accountable government, so that the principle of the rule of law can be effectively implemented in the practice of state administration.